PELATIHAN DASAR-DASAR STATISTIKA DENGAN MENGGUNAKAN APLIKASI MICROSOFT EXCEL DI SDN PAMOTAN II KECAMATAN PORONG - Risdiana Chandra Dhewy (STKIP PGRI Sidoarjo, 2018)
Community service program on basic statistical training by using Ms.Excel application in SDN Pamotan II Kec. Porong is done with the target of the school teacher. It aims to improve teacher insight on the use of already-available computer applications such as Ms. Excel. The use of this application will help a lot of teacher work in the processing of student grades both for filling report cards and school exam grades that originally there are still using manual calculations whereas for now will be used computer applications. The method used includes 3 stages. In the first stage, observations are made to the program objectives of the activity to determine the appropriate method of the target condition and situation. In the second phase of the delivery of training materials that include the introduction of Ms.Excel applications along with functions and statistical formulas to be used in the training. In the third stage, the follow-up activities of further guidance on function and statistical formulas are more varied by teachers. Based on the results of the activity in the form of Ms.Excel application training on the count operation shows that the knowledge of participants and their skills in the operation of the application has increased significantly after being given lectures and practices, so that the activity took place very interesting discussion. The indicators used as a benchmark to increase the knowledge and understanding of the participants is that they have been able to practice the data processing of the students' values used during the activity. In addition, a positive response to this activity was also provided by the participants, as evidenced by the participants' questions during the discussion. The question indicates that the participant understands what the resource person tells you about the operation of the count with Ms.Excel and is a positive thing for additional quality and useful knowledge.